Subperiosteal hematoma from peribulbar block during cataract surgery leading to optic nerve compression in a patient with parahemophilia - Khokhar S; Nayak B; Patil B; Changole MD; Sinha G; Sharma R; Nayak L (International Medical Case Reports Journal, 2015)
Sudarshan Khokhar,1 Bhagabat Nayak,1 Bharat Patil,1 Milind Devidas Changole,1 Gautam Sinha,1 Reetika Sharma,1 Lipika Nayak2 1Dr RP Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India; 2Department of Pediatrics, Loknayak Hospital, Maulana Azad Medical College, Delhi, India Abstract: A 17-year-old male presented with gradual painless diminution of vision since childhood. Slit lamp examination revealed both eyes having congenital cataract. Right eye lens aspiration was performed but was uneventful, and he prepared for left eye surgery after 7 days. Immediately after giving a peribulbar block, a complete akinesia, tight eyelids, and stony hard eyeball was noted. An abaxial proptosis of 7 mm was noted. Lateral canthotomy and inferior cantholysis were done and proptosis reduced to 5 mm. Bleeding time–clotting time was normal. Proptosis worsened to 8 mm the next day. Contrast-enhanced computed tomography scan showed inferolateral subperiosteal hematoma, but drainage could not be performed due to prolonged prothrombin time and activated prothrombin time. Fresh frozen plasma was transfused. Tarsorrhaphy was performed for exposure keratopathy after his coagulation profile became normal. Hematology evaluation after 2 weeks detected factor V deficiency, and was diagnosed as Owren's disease or parahemophilia. Keywords: peribulbar block, hematoma, subperiosteal, parahemophilia, optic nerve compression